Understanding the practices of accounting policy treatment for zakat measurement in Islamic banks the case of Bank Islam Malaysia Berhad / Salaheddin Alasheg - Alasheg, Salaheddin (Institute of Graduate Studies, UiTM, 2018)
Islamic banks play a significant role in redistribution of wealth in society through the implementation of Zakat. These banks aim at providing Islamic financial products and services such as Zakat to their customers in accordance with the Islamic principles and guidelines (i.e., Shariah). Zakat computation is necessary for Islamic banks to fulfil their duty and obligation. The collection of Zakat needs reliable and efficient accounting principles and rules that will provide a proper and fair assessment of the Zakat payment. This study aims to investigate and examine the accounting policy procedure for the determination and measurement of the items included in the Zakat base. In particular, the objectives of this study are (i) to determine whether Bank Islam Malaysia Berhad (BIMB) should or should not use the market-selling price (the current value of the assets) for Zakat payment, (ii) to investigate the accounting basis (cash or accrual basis) that is used for Zakat purpose, and (iii) to examine various schools of thoughts on how the Zakat on debts (accounts receivable - liabilities) should be addressed. For achieving the study objectives, a qualitative content analysis and a single case study were conducted…